Analisis Pengendalian Kualitas Kehilangan Minyak Pada Stasiun Press Dengan Metode Control Chart di PT QRS - Melinda Azzahra Putri; Titis Linangsari; Yuliana Ningsih (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Tanah Laut, 2023)
QRS is one of the palm oil processing industries into Crude Palm Oil (CPO). In every CPO (Crude Palm Oil) processing process, the company always prioritizes the quality of CPO and always optimizes the amount of CPO yield. One of the management systems implemented to obtain the optimal amount of yield is to suppress oil loss during the production process. The dregs in the press station is one of the causes of oil loss. The palm oil mill (PKS) must always ensure that during the process it is within the applicable standards or conditions. PT. QRS has a loss norm of pressed palm oil by 0.52% to FFB at press stations. This study aims to analyze the quality control of oil loss at the press station using the Statistical Process Control (SPC) method with control charts and fishbone diagrams. Based on the results of the control chart, it was concluded that the loss of pressed waste oil at the press station had an average of 0.69% which was still under control, namely UCL (Upper Control Limit) 0.81% and LCL (Lower Control Limit) 0.59%. However, the average oil loss is still above the company's norm of 0.52%. The Fishbone Diagram is used to identify various potential causes that cause loss of waste oil at press stations, including human resources, methods and machines.